Studi Perbandingan Uji Pemadatan Standar dan Uji Pemadatan Modified Terhadap Nilai Koefisien Permeabilitas Tanah Lempung Berpasir - Sembiring, Natanael; Iswan, Iswan; Jafri, Muhammad (Universitas Lampung, 2016)
AbstractConstruction of a construct in civil engineering requires that the material in top shape.The soil that became the foundation of a structure should reach the prime condition to be able to sustain the existing structure on it. But in fact it is not easily met at a project site . This research will compare the compacted soil permeability values are standard with compacted soil permeability values are modified. Soil of the sample in this study were taken from the sukajawa village , Lampung Tengah. The soil was taken from two locations with different types. The soil is then mixed with sand which then compacted using standard methods and methods modified. Permeability testing is done to obtain permeability coefficient. Based on the original soil physical test , AASHTO soil 1 put into groups of A - 7-5 and the second soil into a group of A- 7-6, which means the land is clay soil types and USCS classify the soil into fine-grained soil. The observations in the laboratory showed that compaction with different methods show different results and the amount of a mixture of sand affects the value of soil density.Keywords : Soil clay , sand , compaction and permeability.